Prevalence and significance of mesentery thickening and lymph nodes enlargement in Crohn's disease. Issue 4 (April 2022) - Sampietro, Gianluca M.; Maconi, Giovanni; Colombo, Francesco; Dilillo, Dario; Fiorina, Paolo; D'Addio, Francesca; Loretelli, Cristian; Mantegazza, Cecilia; Nebuloni, Manuela; Corsi, Fabio; Zuccotti, Gianvincenzo; Ardizzone, Sandro; et al.
Abstract : Background: Mesentery thickening and enlarged lymphnodes are typical findings of Crohn's disease (CD), but their role is unknown. Aim of the present study was to evaluate their prevalence and significance on postoperative complications and long-term surgical recurrence after CD surgery. Methods: 1272 consecutive, unselected patients were retrospectively reviewed, divided into 4 groups based on the presence or absence of a thickened mesentery and enlarged lymphnodes, and stratified for primary or recurrent surgical procedure. In all patients but those treated with strictureplasty the mesentery and lymphnodes were removed. Patients' characteristics, peri-operative findings, and long-term recurrence were compared by univariate and multivariate analysis. Results: Thickened mesentery and enlarged lymphnodes were not present in all cases, were typical of ileal location and penetrating behaviour, had a constant decrease over recurrences, were independent of either pre-operative medical therapy or surgical approach, did not increase the duration of surgery and complications, presented similar 20-years recurrence rate to normal mesentery and lymphnodes. Lymphopathy was associated to a worst nutritional status during disease recurrences. At multivariate analysis, age, location, and behaviour, but not mesenteric characteristics, were related to an increased risk of surgical recurrence. Conclusions: This study provides new information on mesentery and lymphnodes in CD patients. Further studies are needed to clarify the appropriate surgical approach.